Evaluating High Performance Liquid Chromatography and Red Cell Indices for Hemoglobinopathy Screening: A Retrospective Study from North India - Bansal, Chakshu; Chopra, Geeta; Singh, Kush Kumar; Singh, Ranveer; Jatale, Raj; Ramchandran, Shibani (Medical Research and Its Applications Vol. 11, 2024)
Globally, as per The World Health Organization, seven percent of the global population are carriers of hemoglobin disorders, with thalassemia and hemoglobinopathies being the most common genetic disorders. Thalassemia and other hemoglobinopathies are also one of the major public health problems in India. As initial screening methods, Red Blood Cell (RBC) indices such as total RBC count, Mean Cell Volume (MCV), Mean Cell Hemoglobin (MCH), Mean Corpuscular Hemoglobin Concentration (MCHC), and Red Cell Distribution Width (RDW) are valuable. High-Performance Liquid Chromatography (HPLC) has emerged as a powerful and excellent tool for the direct identification of different hemoglobin variants. Aim: This study aims to utilize HPLC for identifying various hemoglobinopathies and to analyze the distribution of red blood cell (RBC) indices in different Hemoglobinopathies to assess their significance as screening tests. Materials and Methods: A retrospective study was conducted on 73,333 cases from January 2017 to October 2022. EDTA samples were analyzed on an automated hematology analyzer to determine RBC indices before performing HPLC. The Bio-Rad Variant II CE-HPLC system with the Variant II-Thalassemia short program (Bio-Rad Laboratories) was used to determine different fractions of hemoglobin. Descriptive analysis was used to obtain the frequency and percentage of Hemoglobinopathies in this given Indian population. A two-tailed p-value of <0.05 was considered to be statistically significant. Results: 6,242 (8.52%) cases of abnormal hemoglobin variants were recorded. Beta Thalassemia trait (5.59%) was the most prevalent hemoglobin fraction, followed by HbD Punjab heterozygous, HbE heterozygous, and Sickle cell heterozygous. RBC indices showed statistically significant differences between subjects with normal hemoglobin and those with hemoglobinopathies (p<0.0001). Significant differences in RBC indices were also found between the Beta Thalassemia trait and normal hemoglobin subjects (p<0.0001). The mean RDW value was markedly increased in both Thalassemia syndrome (36.06±6.79) and Hb-E Beta Thalassemia (32.49±6.57). The mean total RBC count was highest in Beta Thalassemia trait (5.07±0.90) and lowest in Beta Thalassemia syndrome (2.71±1.10). Conclusion: RBC indices can be effectively used to screen for Thalassemia and other hemoglobinopathies as a supportive test for High-Performance Liquid Chromatography (HPLC).